Intravenous Immunoglobulins (IVIG) in Chronic Inflammatory Demyelinating Polyneuropathy ( CIDP ): time to maximal recovery. (3rd June 2015) - Baker, S; Opala, A
Abstract : Background: The response of Chronic Inflammatory Demyelinating Polyneuropathy ( CIDP ) to Intravenous Immunoglobulins (IVIG) treatment is well established. However, determination whether patients who do not respond to 2 IVIG treatments or those whose condition stabilizes (ICE Trial) would benefit from additional treatments remains unclear. We aim to identify time period required to reach maximal strength gains from IVIG treatment (plateau). Furthermore, we will assess nerve conduction studies (NCS) changes over time with IVIG treatment. This will help in establishing a time course for treatment of CIDP with IVIG to maximize recovery. Methods: We performed a retrospective chart review of 27 patients with CIDP, with diagnosis confirmed by European Federation of Neurological Societies/Peripheral Nerve Society Guidelines (EFNS/PNS). Each patient's strength response including: grip strength, knee extension, elbow flexion and dorsiflexion (using JAMAR Dynamometer) and NCS changes over time during IVIG treatment were analyzed. The primary outcome is duration of IVIG treatment, in months, required to reach a plateau in strength. Secondary outcome is NCS change including: Terminal Latencies, Conduction Velocities, Compound Sensory and Motor action potentials in nerves of upper and lower extremities over treatment time (emerging trends). Results: Pending (available by April 2015) Conclusion: Pending (available by April 2015)